Improvement in stroke quality management by an educational programme - Behrens, Stephan; Daffertshofer, Michael; Interthal, Cordula; Ellinger, Klaus; Ackern, Klaus van; Hennerici, Michael G. (Cerebrovascular diseases, 2002)
Time after symptom onset in ischaemic stroke has to be as short as possible to increase success of treatment. We prospectively analysed latencies from symptom onset until the start of therapy and the rate of thrombolysis in 196 patients with suspected stroke sequentially admitted to the hospital before (6 weeks prior, n = 83) and after (n = 113) initiating an educational stroke programme (EP). A total of 345 dispatchers, paramedics, and emergency staff were trained, each person for at least 2 h. The mean pre-hospital time interval from symptom onset until admission was significantly decreased by nearly 2 h (p < 0.05). Thrombolytic therapy frequencies increased from 2 to 10.5% (p < 0.01) because the overall mean time interval from admission to the start of therapy significantly decreased (p < 0.01) by 69 min after the EP, with increasing numbers of patients suitable for acute stroke therapies within a 0- to 3-hour treatment window.
Gesehen am 31.03.2021